Continuous Unilateral Cephalalgia Due to Systemic Lupus Erythematosus: A Case Report - Teixeira, Lucas; Cruz, Matheus (Headache Medicine, 2024)
BackgroundHemicrania continua is a rare form of cephalalgia featuring a chronic and persistent headache in only one side of the head.ObjectivesIn this report, we present a case of a patient with hemicrania continua and systemic lupus erythematosus (SLE).MethodsWe collected patient data through the electronic medical record. Afterward, we reviewed the literature regarding hemicrania continua and its pathophysiology and correlation with neurovascular alterations, inflammation, and SLE.ResultsA 42-year-old woman visited the emergency department due to worsening constant unilateral cephalalgia that had been present for the past 6 months. The patient reported a highly intense (10/10) headache in the entire left hemicrania that radiated to the left shoulder. During physical examination, she presented with nystagmus, vertigo, and aggravated cephalalgia associated to body movement and, despite having no optic nerve thickening. In addition, she had jaundice, tachycardia, and splenomegaly. Complimentary exams found deep anemia, depletion in complement system and anti-nuclear factors, suggesting a possible hemolytic anemia (AIHA) due to SLE. Treatment was initiated with hydrocortisone and prednisone, associated with amitriptyline, fluoxetine and diazepam, reaching full remission. These syndromes have aggravated each other, and possibly the explanation for the cephalalgia remission was the control of AIHA and SLE. It features a rare case in literature and thus warrants discussion.